4D seismic reservoir surveillance for a field located in Malaysian basins using different time-lapse seismic attributes - Danaei, S. (European Association of Geoscientists and Engineers, EAGE, 2017)
Time-lapse seismic technology has been used for decades to image fluid flow in oil and gas reservoirs. It shows the movement of reservoir fluids due to production and/or injection activities; therefore, the main objective of this research is to monitor a reservoir during water injection scheme. The reservoir is located in a field in Malaysian basins and has been producing from 2000. In 2006, a repeated 3D seismic survey acquired from the reservoir to monitor the injection process with the baseline seismic survey in 1995. The method is to use basic time-lapse seismic qualitative interpretation to image the water front after six years of water injection. 4D amplitude analysis in conjunction with other seismic attributes are used to monitor the reservoir. 4D sweetness, 4D RMS amplitude, 4D envelope are analysed for the reservoir surveillance. Based on the result of 4D qualitative interpretation, the distribution of injected water is imaged for all injector wells and also areas of remaining oil have been detected. 4D seismic data analysis also has answered a question related to early water breakthrough for one producer well.